A review of the current practice in diagnosis and management of visual complaints associated with concussion and postconcussion syndrome. Issue 5 (September 2016) - Heinmiller, Laura; Gunton, Kammi B.
Abstract : Purpose of review: Concussions and their related sequelae have received significant attention given the high-profile media coverage from professional sports and recreational leagues. A better understanding of the diagnosis and symptom management may limit the long-term impact these injuries have on the affected individual. The aim of this review is to provide updated information for both diagnosis and ongoing management for visual symptoms of concussions. Recent findings: New testing including a brief vestibular/ocular motor screening assessment and the importance of near point of convergence measurements may prove beneficial to the diagnosis and identification of patients at greater risk for developing postconcussion syndrome. Additionally, the development of postconcussion syndrome is more likely when symptom burden is greater upon presentation. Summary: Currently, there is not a single testing method that can universally identify all individuals with concussion. Current management of concussion focuses on targeted treatment based upon symptoms and signs present at onset to decrease disease burden and help restore baseline functioning as soon as possible.